165k views
0 votes
Please explain also! I am not here just to get answers, I am here to understand. Thank you!

Please explain also! I am not here just to get answers, I am here to understand. Thank-example-1
User Notaras
by
4.8k points

1 Answer

6 votes

To help solve this, we need to use the slope formula.

(y2 - y1) / (x2 - x1). We get these values by picking two points on a line.

For JL, we will pick points (-5, -3) and (-2, -4).

y1 = -4

y2 = -3

x1 = -2

x2 = -5.

Let's plug these into our formula.

(-3) - (-4) / (-5) - (-2) = -1/3

For LN, we will pick points (-2, -4) and (7, -7).

y1 = -7

y2 = -4

x1 = 7

x2 = -2.

Lets plug these values into our equation.

(-4) - (-7) / (-2) - (7) = -1/3

Therefore,

(-3) - (-4) / (-5) - (-2) = (-4) - (-7) / (-2) - (7)

The correct answer is G.

User Asim Shahzad
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.